Baskara Fashion Design Inspired by Kretek Dance from Kudus with Neo-eco Theme and Woven Elements - Choirina, Rofiatul; Kusumastuti, Adhi (Journal of Creativity Student, 2026)
The development of a culture-based and sustainable fashion industry has opened up new opportunities in men's fashion design. However, the exploration of men's fashion that integrates traditional cultural elements and environmentally friendly concepts is still relatively limited. This study aims to design ready-to-wear men's clothing inspired by the Kretek Kudus dance, applying weaving techniques and the neo-eco concept as a sustainable approach. The research method used is development research by applying the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The Kudus Kretek Dance is used as a source of visual and philosophical ideas, while weaving is applied as an aesthetic element as well as a cultural character enhancer in clothing. The design results are manifested in a set of men's clothing consisting of an outer, shirt, pants, and sarong. Product feasibility testing was conducted by three expert panelists using six assessment indicators. The assessment results showed that the indicators of aesthetics, clothing performance, and uniqueness were in the highly feasible category, while the indicators of design, size, and sewing technique were in the feasible category. These findings indicate that the integration of the cultural elements of the Kretek dance, weaving, and the neo-eco concept can produce men's clothing that is aesthetic, functional, and sustainable.